Lithium-ion batteries hazard and use assessment - Mikolajczak, Celina; Kahn, Michael; White, Kevin; Long, Richard Thomas (Springer, 2011)
Suitable for practitioners, this book examines the usage of lithium-ion batteries and cells within consumer, industrial and transportation products, and analyzes the potential hazards associated with their prolonged use. It also surveys the applicable codes and standards for lithium-ion technology